2018
DOI: 10.5194/se-9-39-2018
|View full text |Cite
|
Sign up to set email alerts
|

On the link between stress field and small-scale hydraulic fracture growth in anisotropic rock derived from microseismicity

Abstract: Abstract. To characterize the stress field at the Grimsel Test Site (GTS) underground rock laboratory, a series of hydrofracturing and overcoring tests were performed. Hydrofracturing was accompanied by seismic monitoring using a network of highly sensitive piezosensors and accelerometers that were able to record small seismic events associated with metre-sized fractures. Due to potential discrepancies between the hydrofracture orientation and stress field estimates from overcoring, it was essential to obtain … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 67 publications
3
47
0
Order By: Relevance
“…Schorlemmer et al (2005) examined the b values of earthquakes in different stress regimes and found that lower values correlated with areas of higher differential stress. Similar trends have been reported for induced seismicity (Bachmann et al, 2012) but also in tectonic earthquakes (Tormann et al, 2014(Tormann et al, , 2015Spada et al, 2013) and laboratory experiments (Amitrano, 2012;Goebel et al, 2012). Thus, it was hypothesized that b values are related to local stress conditions (Scholz, 2015), or -in the context of induced earthquakes -to a combination of pressure and stress conditions.…”
Section: Induced Seismicitysupporting
confidence: 67%
See 2 more Smart Citations
“…Schorlemmer et al (2005) examined the b values of earthquakes in different stress regimes and found that lower values correlated with areas of higher differential stress. Similar trends have been reported for induced seismicity (Bachmann et al, 2012) but also in tectonic earthquakes (Tormann et al, 2014(Tormann et al, , 2015Spada et al, 2013) and laboratory experiments (Amitrano, 2012;Goebel et al, 2012). Thus, it was hypothesized that b values are related to local stress conditions (Scholz, 2015), or -in the context of induced earthquakes -to a combination of pressure and stress conditions.…”
Section: Induced Seismicitysupporting
confidence: 67%
“…Bachmann et al (2011) and Mena et al (2013) developed several statistical models and tested them in a pseudo-prospective manner using the Basel seismicity dataset. More complex models including physical considerations and stochastic processes (so-called hybrid models) were developed to include information on the reservoir behavior and from the spatiotemporal evolution of seismicity (Goertz-Allmann and Wiemer, 2013;Kiràly et al, 2018). Mignan et al (2015) evaluated reported insurance claims arising from the Basel induced seismicity in order to infer procedures for evaluating risk based on induced seismic hazard estimates.…”
Section: Induced Seismicitymentioning
confidence: 99%
See 1 more Smart Citation
“…The feasibility to monitor fracture processes of hydraulic fracturing in situ were demonstrated by Eisenblätter (1988), Niitsuma et al (1993), and Manthei et al (2003). The results from recent in situ experiments showed the efficiency of combined seismic monitoring (Gischig et al, 2018;Kwiatek et al, 2011;López Comino et al, 2017;Nakatani et al, 2008;Plenkers et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Also, at the Basel geothermal project, a 400-fold irreversible permeability enhancement was observed after stimulation (Häring et al, 2008). Since during HF, permeability enhancement tends to be reversible, permanent fracture opening is achieved in shale gas fields by flushing sand or other particles (proppants) into the fractures along with the fluid (Gidley et al, 1989 geothermal energy exploitation, HS is the favored method because no proppant, or chemical additives to increase fluid viscosity for better proppant spreading, have to be used.…”
Section: Introductionmentioning
confidence: 99%